Estudo de massas de porcelanato esmaltado contendo filito como fundente - Brasileiro, Camila Tavares (Universidade Federal de São Carlos, 2020)
The production of ceramic tiles is growing worldwide and Brazil is the third-largest producer in the world. Porcelain tiles represent a significant fraction of this production and the trend is for significant growth in the market for this type of product in the coming decades. This scenario is marked by the increasing demand for raw materials. However, the progressive depletion of the main deposits of feldspar leads the ceramic industry to look for substitutes for this flux. A considerable part of the Brazilian industry, for several reasons, has already replaced feldspar, traditionally used as a fluxing agent, with phyllite, consisting basically of quartz, kaolinite, and sericite. Brazil is the only country that uses phyllite in the glazed porcelain masses. This gives the Brazilian industry an important competitive advantage in this segment. However, as other producers use feldspar, there are practically no studies on the effects of replacing feldspar with sericite in glazed porcelain tiles compositions. Initial studies showed very significant differences in the behavior of glazed porcelain masses containing the same content of feldspar and phyllite during firing. Based on this, the objective of this thesis was to identify how the mineral through which the fluxing ions are introduced into the porcelain composition affects its behavior during firing. In an unprecedented way, this work formulates a feldspar composition with the same flux content as the phyllite (synthetic phyllite with feldspar) with the same chemical composition and assesses its implications. The search for explanations for the observed differences was based mainly on the volume and characteristics of the liquid phase developed at high temperatures. The results showed that 1) the liquid phases produced by the fusion of sericite and feldspar play a central role in explaining the differences in behavior during heating, 2) the origin of the differences is mainly in the transformations that occur between 950 and 1150 ºC, e) differences at relatively low temperatures are also explained by the effect of granulometry.
Study of glazed porcelain tiles bodies containing phyllite as flux
Keywords: Porcelanato; Minerais fundentes; Sericita; Fluxo viscoso; Gresificação; Porcelain tile; Fluxing minerals; Sericite; Viscous flow; Vitrification; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS